Enantiopure cis- and trans-2, 5-disubstituted-2, 5-dihydrofurans from d-allal- and d-galactal-derived vinyl epoxides. Issue 33 (16th August 2019) - Di Bussolo, Valeria; Princiotto, Salvatore; Bordoni, Vittorio; Martinelli, Elisa; Favero, Lucilla; Crotti, Stefano; Uccello Barretta, Gloria; Balzano, Federica; Pineschi, Mauro; Crotti, Paolo
Abstract: Upon treatment with the metal enolates of methylene active compounds (dimethyl malonate and dibenzoylmethane) ( C -nucleophiles) and benzyl carbamate ( N -nucleophile), d -allal- andd -galactal-derived vinyl epoxides are stereoselectively transformed, in a single step, into diastereoisomeric, highly functionalized, enantiopure cis - and trans -2, 5-disubstituted-2, 5-dihydrofurans. Graphical abstract: Image 1